Bissu Rituality on Bugis Community in Sub District Segeri Pangkep Regency South Sulawesi - Hasriani, Andi (Tun Dr. Mahathir Mohamad Thoughts Institute (IPDM), 2018)
Bissu is a cultural trace of the pre-Islamic Bugis tribe that still survive until now, who served as guard of arajang heirlooms. Bissu is not a transvestite or a calabai, but a person who is immune to sharp weapons, who are also able to communicate with the Gods by using the to rilangi language. This research is focused on the ritual event performed by bissu which is mappalili and maggiri dance which still exist although faced with various challenges such as the influence of Islamic teachings, the dynamics of the life of a growing society, and the change of ceremonial status is done become a custom or just as a cultural staging that is expected to attract tourists to come to see the ritual event. The method used in this research is qualitative method which starts with observation, location determination, sample determination, interview, data processing and writing of research result. Result of research about bissu ritual in Segeri regency of Pangkep, illustrates that the local government still support the existence of bissu as a leader in the mappalili ritual performed every year before the rice fields that end with maggiri dance ritual as the peak event is still expected to exist as a preserver of regional culture as well as the culture of the archipelago.